Analysis of Learning and Growth, Business Processes, Costs and Service Innovation on Customer Loyalty with Customer Satisfaction as an Intervening Variable - Ronaldo Simanjuntak; Hery Margono (Majalah Ilmiah Bijak, 2022)
The aims of this study were to 1) analyze the effect of learning & growth, business processes, costs, service innovation on customer satisfaction at RSAB Harapan Kita partially or simultaneously; 2) analyze the effect of customer satisfaction on customer loyalty at RSAB Harapan Kita; and 3) knowing the effect of learning & growth, business processes, costs and service innovation on customer loyalty with customer satisfaction as an intervening variable at RSAB Harapan Kita. This study uses a quantitative approach with multiple linear regression analysis techniques. The population in this study was patients, which included outpatients at RSAB Harapan Kita in 2020. The sampling technique used was a non-probability sampling technique with an accidental sampling approach, so that 97 respondents were obtained. The data collection technique used a closed questionnaire with a measurement scale using a five-point Likert scale. The results of the study can be concluded that overall there is an effect of learning, business processes, costs and innovation (variable X) on loyalty (Y) through customer satisfaction (Z).